An English-language Multimedia Teaching Model Based on Krashen’s Theory - Yuan, Fang (International Journal of Emerging Technologies in Learning (iJET), 2018)
Traditional English teaching practice often centers on the teacher and implements the teaching mode of “exemplifying by the teacher-answering by students-evaluating by the teacher”. This inflexible teaching mode fails to fully exert student’s subjective function; at the same time, due to the lack of necessary guidance and help from teachers, students are more likely to suffer from learning burnout and low self-confidence. With this regard, an English multimedia teaching mode was proposed in this study based on Krashen’s “Language Input Theory”. The theory is characterized by emphasizing the analysis of English language learning from the perspectives of “acquisition” and “learning”, advocating “understanding” of knowledge and using student-centered teaching methods. In this study, Krashen’s theory was combined with interactive learning methods and multimedia information technology to form an English teaching mode focused on “teacher-student”, “student-student” and “student-computer” interactions and build an “in class- after class” and “online-offline” English learning environment. This mode was practically applied in the teaching of “College English” at Hohai University in Jiangsu Province, China. The results show that the English multimedia teaching mode based on Krashen’s theory is more effective than the traditional teaching mode in improving students’ interest and self-confidence in learning.